Examining the Influence of Product Quality and Pricing on Customer Satisfaction: A Case Study of "Dange" Cake in Pangkep Regency - Sabahannur, St; Maylafaizza, Salsabila; Adam, Andi Maslia Tenrisau (Jurnal Agrinika: Jurnal Agroteknologi dan Agribisnis, 2024)
Dange Cake, a distinctive delicacy originating from the Pangkep Regency community, is crafted from primary ingredients such as black or white glutinous rice, coconut, and brown sugar. The Dange Cake enterprise has emerged as a promising venture for the local populace. This research endeavors to assess the impact of product quality and pricing on customer satisfaction levels concerning Dange Cake within the region. Employing multiple linear regression as the analytical method, the study seeks to quantify the degree of influence exerted by product quality and pricing on customer satisfaction. The investigation reveals the presence of two variants of Dange Cake, namely White Dange and Black Dange, retailed at IDR15,000 per box for each variant. The Dange Cake Sabah enterprise has succeeded in amassing a monthly revenue of IDR78,000,000, offset by a total production expenditure of approximately IDR37,647,500, thereby yielding a net profit of IDR40,352,500. A business feasibility assessment demonstrates a R/C Ratio of 2.07, underscoring the profitability and viability of the Dange Cake enterprise. Consumer perceptions pertaining to the quality and pricing of Dange Cake in Dange Sabah are overwhelmingly positive, with patrons enjoying its delectable flavor, distinctive texture, and reasonable pricing. Furthermore, commendations are extended towards product packaging and employee service, both of which receive high acclaim from consumers. The significance values associated with the product quality and pricing variables underscore their profound influence on customer satisfaction, with significance values of 0.000 <0.05.